2020
DOI: 10.24127/pro.v8i1.2868
|View full text |Cite
|
Sign up to set email alerts
|

Guru Menginovasi Bahan Ajar Sebagai Langkah Untuk Meningkatkan Hasil Belajar Siswa

Abstract: Teachers are professions that require special expertise in their main tasks such as educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education in formal, primary and secondary education. Teachers apart from the assignment also design learning to help students in the learning process, so teachers need special expertise and high ability to develop teaching materials that are appropriate to the needs of students with the diversity of students' competence. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
0
11
0
10
Order By: Relevance
“…Another study [21] found that the entrepreneurship module at SMA Negeri 1 Menganti Gresik had a significant influence on student learning outcomes before and after it was implemented. According to the findings of another study [17], teacher-made visual aids facilitate student understanding and improve learning outcomes. In addition, it was also discovered [22] that higher OSCE scores in the intervention group, indicating that the new module designed by the researchers effectively increased the knowledge and skills of medical students regarding evidence-based infant feeding practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study [21] found that the entrepreneurship module at SMA Negeri 1 Menganti Gresik had a significant influence on student learning outcomes before and after it was implemented. According to the findings of another study [17], teacher-made visual aids facilitate student understanding and improve learning outcomes. In addition, it was also discovered [22] that higher OSCE scores in the intervention group, indicating that the new module designed by the researchers effectively increased the knowledge and skills of medical students regarding evidence-based infant feeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…A study [17] has found that expert judgment determines the validity of teaching materials in research and development. Two nutrition experts who are also lecturers in the DIII Nutrition Study Program, Kendari Health Polytechnic and one lecturer who has experience in making teaching materials, evaluated the development of this module.…”
Section: Expert Team Evaluation Of Advanced Dietetics Modulementioning
confidence: 99%
“…Until now, the teacher teaches from the French learning resources that are already available such as trend method book, Google and YouTube. Learning materials that are developed by others is less suitable for students [20] . Because these materials are not suitable for the characteristics of the students, and only the teacher knows more about the characteristics of the students.…”
Section: Analysis Stagementioning
confidence: 99%
“…One of the things that affects the quality of learning is teaching materials, if the teaching materials available are inadequate and inappropriate, it will be difficult to create quality learning. Teaching materials are an important source of material for students in carrying out the learning process (Suprihatin & Manik, 2020).…”
Section: Learning Qualitymentioning
confidence: 99%